Potret dan Prospek Kajian Uṣūl Al-Tafsīr dalam Perkembangan Tafsir Al-Qur’an - Amin, Ahmad Syaifuddin (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2021)
Abstract: Containing muti-interpretative text, al-Qur’an as the main text in Islam has been interpreted in varoius methods producing too much interpretation result. Not only protected in the authenticity, al-Qur’an should be protected by correct interpretations. Without the proper ones, its function as hudan li al-nās will not be realized. Unfortunately, Uṣūl al-tafsīr as a discipline that protects the validity of interpretation was not as popular as other diciplines like nahw and uṣūl fiqh. This article discusses uṣūl al-tafsīr as an academic discipline taking strategic position is Islamic studies. By studying some literatures, this article concludes that uṣūl al-tafsīr is a part of ulūm al-Qur’ān that is focused on the ways, methods and rules of how al-Quran should be interpreted. Even uṣūl al-tafsīr has been established during prophet’s era, uṣūl al-tafsīr was developed significantly in the 8th century AH which marked by the emergence of books of ulūm al-Qur’ān. Passing more various problems in contemporary era, scholars should develop the studies and research on uṣūl al-tafsīr.